PENGARUH INTELLECTUAL CAPITAL, CORPORATE SOCIAL RESPONSIBILITY DAN UKURAN PERUSAHAAN TERHADAP KINERJA PERUSAHAAN - Dimas Syafi (2020)
This research is a quantitative study that aims to determine the effect of intellectual capital, corporate social responsibility and company size on company performance. This study uses annual reports of companies in the basic and chemical industry sectors listed on the Indonesia Stock Exchange in 2017-2018 as samples prepared based on purposive sampling techniques. Tests in this study used Multiple Linear Regression Analysis with SPSS analysis tools and a significance level of 5% (0.05). The results obtained (1) there is a positive influence of intellectual capital on company performance, (2) there is a positive influence on corporate social responsibility on company performance, (3) there is a negative influence on company size on company performance.